Pengaruh Pendidikan Kesehatan Media Audio Visual terhadap Pengetahuan Gawat Darurat pada Remaja Sekolah di Kota Singkawang - Muzaki, Haekal Alam; Kapadia, Raju; Agustina, Mita; Susito, Susito (Bima Nursing Journal, 2024)
Background: Health education regarding Basic Life Support (BHD) is really needed for all groups because an emergency is a situation that can happen anywhere, at any time and to anyone. The importance of health education is to identify heart attack patients early as a link in the chain of survival before going to hospital (pre-hospital). Therefore, everyone can be a savior for cardiac arrest victims, from teenagers to adults, armed with Basic Life Support (BLS) knowledge. Purpose: untuk mengetahui pengaruh pendidikan kesehatan bantuan hidup dasar (BHD) melalui media audiovisual terhadap peningkatan pengetahuan siswa SMA. Method: This research method uses a quantitative approach with a pre-test and post-test design without a control group using a preexperimental design without a comparison group. The sample used was 36 respondents from class XII MIPA 3 SMA Negeri 3 Singkawang City using total sampling techniques. Results: Shows that respondents experienced an increase in knowledge (post-test) as evidenced by the results of the Wilcoxon statistical test which obtained a p value of 0.000 (p < 0.05). This shows that health education through audio-visual media has a significant influence on the level of knowledge of students and students regarding basic life support (BHD at SMA Negeri 3 Singkawang. Conclusion: In this research there is an influence of health education through audio visual media about basic life support (BHD) on the level of knowledge of students and students of class XII MIPA 3 SMA Negeri 3 Singkawang